2021
DOI: 10.3390/app11115052
|View full text |Cite
|
Sign up to set email alerts
|

Fe2O3 Nanowire Flux Enabling Tungsten Inert Gas Welding of High-Manganese Steel Thick Plates with Improved Mechanical Properties

Abstract: Economic welding of thick steel plates is an emerging challenge for various engineering applications. However, tungsten inert gas (TIG) arc welding, as an economic and widely used method, is not regarded as a suitable tool to weld thick steel plates due to the shallow penetration in a single-pass operation. In this technical progress, the joining of austenitic high manganese steel of 8 mm thickness was successfully performed using nanowire flux activated TIG welding with a full penetration and a narrow bead ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…They concluded that enhanced current provided enhanced ultimate tensile strength. Zhang et al [14] investigated the combining of 8 mm of thick austenitic high manganese steel adopting a nanowire flux-activated TIG process. They detected that relative to micro flux, nanowire flux significantly improved intake energy efficiency, tensile strength, or even strain due to strong reversal Marangoni convection and reduced melting temperature of nanowire flux among melting pool.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that enhanced current provided enhanced ultimate tensile strength. Zhang et al [14] investigated the combining of 8 mm of thick austenitic high manganese steel adopting a nanowire flux-activated TIG process. They detected that relative to micro flux, nanowire flux significantly improved intake energy efficiency, tensile strength, or even strain due to strong reversal Marangoni convection and reduced melting temperature of nanowire flux among melting pool.…”
Section: Introductionmentioning
confidence: 99%